The whole‐cell Ca2+ release‐activated Ca2+ current, ICRAC, is regulated by the mitochondrial Ca2+ uniporter channel and is independent of extracellular and cytosolic Na+ - Samanta, K; Bakowski, D; Amin, N; Parekh, A (Wiley, 2019)
Ca2+ entry through store‐operated Ca2+ release‐activated Ca2+ (CRAC) channels plays a central role in activation of a range of cellular responses over broad spatial and temporal bandwidths. Mitochondria, through their ability to take up cytosolic Ca2+, are important regulators of CRAC channel activity under physiological conditions of weak intracellular Ca2+ buffering. The mitochondrial Ca2+ transporter(s) that regulates CRAC channels is unclear and could involve the 40 kDa mitochondrial Ca2+ uniporter (MCU) channel or the Na+–Ca2+–Li+ exchanger (NCLX). Here, we have investigated the involvement of these mitochondrial Ca2+ transporters in supporting the CRAC current (ICRAC) under a range of conditions in RBL mast cells. Knockdown of the MCU channel impaired the activation of ICRAC under physiological conditions of weak intracellular Ca2+ buffering. In strong Ca2+ buffer, knockdown of the MCU channel did not inhibit ICRAC development demonstrating that mitochondria regulate CRAC channels under physiological conditions by buffering of cytosolic Ca2+ via the MCU channel. Surprisingly, manipulations that altered extracellular Na+, cytosolic Na+ or both failed to inhibit the development of ICRAC in either strong or weak intracellular Ca2+ buffer. Knockdown of NCLX also did not affect ICRAC. Prolonged removal of external Na+ also had no significant effect on store‐operated Ca2+ entry, on cytosolic Ca2+ oscillations generated by receptor stimulation or on CRAC channel‐driven gene expression. In the RBL mast cell, Ca2+ flux through the MCU but not NCLX is indispensable for activation of ICRAC.